GAS CHROMATOGRAPHY-MASS SPECTROMETRY (GC-MS) ANALYSIS OF COMMERCIALLY AVAILABLE HERBAL AND NON-HERBAL TOOTHPASTES - MUTHU, DR. R.M. THERRADDI; MANIGANDAN, DR.T.; JONES, DR. SUMATHI (South Eastern European Journal of Public Health, 2024)
Toothpaste formulations, both herbal and non-herbal, contain a variety of components, including abrasives, sweeteners, and detergents, which influence their effectiveness and safety. This study compared the composition of commercially available herbal (Dabur Red, Vicco Vajradanti) and non-herbal (Colgate Strong Teeth, Pepsodent Germicheck) toothpastes in India using Gas Chromatography-Mass Spectrometry (GC-MS). The analysis focused on the concentration of abrasive agents, sweeteners, and other key ingredients. Results indicated that non-herbal toothpastes, particularly Colgate Strong Teeth and Himalaya Complete Care, had higher levels of calcium carbonate, hydrated silica, sorbitol, and sodium saccharine, contributing to increased abrasivity. Herbal toothpastes contained lower concentrations of these agents, suggesting a gentler formulation. Fluoride and potassium nitrate, with anti-cariogenic and anti-hypersensitivity properties, were exclusive to Colgate. This study highlights the need for balance between cleaning efficiency and safety in toothpaste formulations, emphasizing the distinct properties of herbal and non-herbal products. .